David Inshaw - Lambirth, Andrew 1959- (Unicorn Press, 2015)
David Inshaw paints pastoral images, often imbued with a sense of mystery and emotional depth. He also paints figures, nude or clothed, with an evident relish and sense of celebration. His appreciation of the individuality of his models is manifest in these paintings, which show a human warmth and breadth of understanding
Keywords: Inshaw, David 1943- / Criticism and interpretation; Inshaw, David -- 1943-; Geschichte 1943-2015; Zeichnung; Malerei